The Effect of Play Therapy on the Level of Anxiety Due to Hospitalization in Pre-School Children at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Tresya Rosita Runtuwene; Andi Akifa Sudirman; Lenny Ali (Universitas Muhammadiyah Palu, 2026)
Preschool-aged children who are undergoing hospitalization can cause anxiety caused by changes in atmosphere, pain felt by children and environments that are unfamiliar to them. So it is necessary to take quick action to overcome this so that children become more comfortable and cooperative with medical personnel so that the treatment process is not hampered, namely by playing therapy coloring pictures. The purpose of this study was to determine the effect of play therapy on the level of anxiety due to hospitalization in preschool-age children at Prof. Dr. H. Aloei Saboie Hospital, Gorontalo City. Types of quantitative research. The research design was done with the Pre-Experimental method with the One group pre-post test approach. A sample of 22 children was selected using the Purposive Sampling technique. The instruments used were Depression Anxiety Stress Scales (DASS) and SOP therapy to play coloring pictures. Statistical test using paired t-test. The results obtained were the average anxiety level before 17.82 and after 10.68, and a significant value of 0.000 (p<0.05). It was concluded that there was an effect of play therapy on the level of anxiety due to hospitalization in preschool-age children at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City.